Relational education, successful pilot plan or a bad public policy implemented (2019)
Education is one of the most important aspects when analyzing the public policies of a territorial entity, for the case of this document an analysis is made of the process of implementation of the model of Relational Education that has been taking place in some educational institutions of the Department of Cundinamarca. For the understanding of the arguments of this writing it must be taken into account that the evolution in this aspect has not been given to the step of the advances in other areas and that many experts have recommended to the Colombian State to transform the way of work in the classrooms. On the other hand, some crises and resistances are identified in the educational communities in which the new educational model is implemented, this paper makes visible the perceptions and impacts that the process has generated not only in the actors directly involved, but also in a collateral way the impact in the communities that are in the immediate contexts of educational institutions. The document recognizes the importance of the characteristics of the context, the need for permanent accompaniment, a gradual implementation and the realization of adjustments according to what is constructed in an open dialogue between the representatives of the public policy implemented and the focused community.